Rainfall, Runoff, Soil and Nutrient Loss Relationships Under Cassava+Pineapple Strip Cropping in Humid Tropical Kerala, India - Surendran, U; Maria, C Lintu; Joseph, E. J (JOURNAL OF ROOT CROPS, 2014)
In many regions of the humid tropics of Kerala, nutrient losses due to soil erosion are extremely large because of the sloping terrain coupled with heavy rainfall. This is one of the main factors limiting soil fertility and crop yields. Hence the present study was taken up to assess the runoff, soil loss and subsequent nutrient losses in cassava and pineapple strip cropping in humid tropical Kerala. Treatments included cassava alone and cassava with pineapple strip cropping. The surface runoff of different rainfall events (classified as low, medium and high) was collected in the first tank, which overflowed into a second tank via a multi-slot (thirteen-slot) devisor that allowed the overflow into the other tank. Volume of flow collected in these tanks was considered as plot runoff. The total amount of eroded soil was estimated by filtration of a composite sample collected from both the tanks after thoroughly mixing the runoff and sediment collected in them. The dried samples were analyzed for C, N, K, Ca and Na by adopting standard methodologies. The results indicated that the soil loss of cassava alone plot was high (0.13-139.00 t ha-1), whereas in the cassava and pineapple strip cropping it was 0.0-8.28 t ha-1 for different rainfall events of low to high. The nutrient content in the eroded soil was significantly greater than the initial soil nutrient content of these plots, indicating that the eroded particles were finer in composition. The quantity of nutrient loss was significantly greater under cassava alone plot due to greater quantity of runoff and eroded soil. The study indicated that cassava + pineapple strip cropping was an effective strategy for arresting the soil erosion from cassava fields under steep slopes.